The Influence of Product Quality and Price on Consumer Satisfaction of SGM Milk Products in Palembang - Ilham, Namira Putri Amalia; Lestari, Retno Budi (Sean Institute, 2025)
This study aims to analyze the Influence of Product Quality and Price on Consumer Satisfaction with SGM Milk Products in Palembang. This research uses a descriptive quantitative method with a sample of 100 respondents. The sample in this study consists of consumers (parents, siblings, or other family members) who purchase SGM Milk products at G&G Milk Store, MM Jaya Indah Kertapati, Toko Miring, Toko Restu Embun, and Toko Intan.The data analysis method uses non-probability sampling, quota sampling, and multiple regression with the SPSS version 26 tool. Based on the research results, it shows that the variables of Product Quality and Price have a significant and positive partial and simultaneous effect on Consumer Satisfaction with SGM milk products in Palembang.